2004
DOI: 10.1063/1.1783013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transmission of microwave radiation in one-dimensional metallic gratings with subwavelength aperture

Abstract: The transmission enhancement of microwave radiation through subwavelength apertures in metallic structures with double-sided gratings was analyzed. It was observed that the structures displayed enhanced transmission around surface plasmon resonance frequencies. It was also observed that the normalized transmission decreased sharply with increased reception angle. It was found that the grating structures exhibited best results with ∼50% transmission at 20.7 mm, enhancement factor of ∼25 and ±4° angular divergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 15 publications
(14 reference statements)
1
53
0
1
Order By: Relevance
“…There have been subsequent theoretical and experimental studies of this aperture -groove structure [10][11][12][13][14] , but there have been very few attempts to integrate this structure into an active device [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…There have been subsequent theoretical and experimental studies of this aperture -groove structure [10][11][12][13][14] , but there have been very few attempts to integrate this structure into an active device [15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these systems can be used as filters by just tuning the periodicity [2]. A full analysis of the dependence of such resonances on other geometrical parameters is also available in the literature for systems like hole arrays [3] and apertures surrounded by corrugations [4,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent investigations of SPR in metallic structures showed enhanced transmission in the visible frequency range through nano-scale SSA fabricated in an Ag film patterned with periodic corrugations on the surface [13]. Implementing a similar concept at microwave frequencies is difficult because SPRs cannot be excited on the surface of common metals which can be considered as perfect conductors in this frequency range [14]. By placing split ring resonator (SRR) at the near field of a SSA in a copper plate, Aydin et al experimentally demonstrated impressive enhanced transmission around 3.7 GHz, in which no SPR effects was involved [15].…”
Section: Introductionmentioning
confidence: 99%